Fueling teen athletes: Parents top concerns about nutrition - Cullicott, L. (Austin Fit Magazin, 2024)
The passionate dedication to sports in Texas is deeply rooted in its history. The state boasts a rich high school football tradition that borders on legendary. But it`s not just football - it`s soccer, tennis, basketball, baseball, volleyball, and golf, and then the non-ball sports of running, swimming, cycling, gymnastics, and rowing, to name just a few. Chances are, if you have a child, that child is involved in at least one sport - or several!